ORGANIC SILICON IN THE PRODUCTION OF ITALIAN ZUCCHINI - Secco Araujo, Mateus (Journal of Interdisciplinary Debates, 2021)
The use of silicon in several crops has been shown to be beneficial because of its protection in the leaves, reducing the attack of pests and diseases, because of which there is a significant increase in the production of various crops. The objective of this study was to evaluate the influence of the application of silicon drench with different application rates on the production of Italian zucchini plants of the Caserta grow crops conducted in an open environment. Different drenches of silicon were evaluated to prevent and reduce the incidence of pathogens, increasing productivity. The experiment was carried out in the garden of the Hospital São Roque in the city of Getúlio Vargas - RS, using the seeds of Italian zucchini of the Caserta grow crops, with different drenches of silicon. Weight, circumference and size of the fruits of zucchini were evaluated. Seed treatment with silicon, T3: Seed treatment with silicon + 1 silicon application via leaf (0.5L ha-1), T4: Seed treatment with silicon, T3: Seed treatment with silicon + 2 applications of foliar silicon (each application 0.25L ha-1), T5: 1 application of foliar silicon (0.5L ha-1) and T6: 2 applications of foliar silicon The response variables were submitted to the variation analysis and to the Duncan test at 5% of probability for the comparison of averages. the use of silicon in the treatment of seeds and a single foliar application, presented a reduction in fruit circumference, in relation to the plants that did not receive silicon application, being that these plants also presented a reduction in fruit length in relation to plants that received Si in the treatment of seeds and two foliar applications, with half a dose each.